Role of ACE2 and TMPRSS2 polymorphisms on COVID-19 outcome and disease severity in adult patients: A prospective cohort study in a tertiary hospital, Indonesia - Yunita, Rina; Wahyuni, Arlinda S.; Sinaga, Bintang YM.; Yamamoto, Zulham; Soebandrio, Amin; Kusumawati, R. Lia; Sembiring, Rosita J.; Pandia, Pandiaman (Narra J, 2024)
Coronavirus disease 2019 (COVID-19) has led to a significant number of infections and deaths worldwide, yet its pathogenesis and severity remain incompletely understood. Angiotensin-converting enzyme 2 (ACE2) and transmembrane protease, serine 2 (TMPRSS2), play crucial roles as receptors and molecules responsible for the virus's entry into host cells, initiating the infection process. Their polymorphisms have been extensively studied in relation to COVID-19 severity. The aim of this study was to examine the association of ACE2 (rs2074192) and TMPRSS2 (rs12329760) polymorphisms with COVID-19 outcome and severity. A prospective cohort study was conducted in 2022 at Haji Adam Malik Hospital, Medan, Indonesia. We randomly recruited hospitalized adult patients with COVID-19, confirmed by real-time polymerase chain reaction (RT-PCR). The baseline demographic data, disease severity, underlying disease, comorbidities, and COVID-19 vaccination status were collected. The single-nucleotide polymorphism (SNP) was assessed using TaqMan SNP genotyping assay, and the levels of TMPRSS2 and ACE2 proteins were measured using enzyme-linked immunosorbent assay (ELISA). A total of 151 COVID-19 patients were recruited and there were significant associations between age and severity with mortality outcomes. The age, kidney and lung diseases, and vaccination status were associated with severity levels. The results showed the CC genotype of ACE2 had the highest proportion, followed by TT and CT genotypes among patients, while CT was the most prevalent genotype, followed by CC and TT for TMPRSS2. This study did not find a significant association between ACE2 and TMPRSS2 genetic variants with disease severity and outcome but highlighted a specific association of TMPRSS2 SNP with mortality within the group. In addition, ACE2 concentration was significant different between mild-moderate and severe-critical COVID-19 groups (p=0.033).